A study of prevalence of thyroid dysfunction in patients with metabolic syndrome - Senthil, N.; Thomas, Sneha; Santosh, P.; S, Sujatha. (International Journal of Research in Medical Sciences, 2017)
Background: The study was undertaken with an objective to study the thyroid functions in patients with metabolic syndrome diagnosed as per International Diabetes Federation (IDF) criteria and to know the spectrum of thyroid dysfunction. Methods: A total of 300 patients with metabolic syndrome diagnosed as per IDF criteria were included in the study. A detailed history regarding symptoms of hypothyroidism and examination was done in all patients and all these patients underwent thyroid profile tests. Results: A total of 300 patients with metabolic syndrome were included in this study. Thyroid dysfunction was present in 45% of the patients. Hypothyroidism was noted in 43 patients, subclinical hypothyroidism was noted in 114 patients, subclinical hyperthyroidism in 6 patients and hyperthyroidism in 1 patient. This study included 166 males and 134 females. 10% of the patients had symptoms related to hypothyroidism. 7% had goiter on examination. Thyroid dysfunction was seen in 68% females compared to that of 47% in males. Females had higher incidence compared to males. Elderly females (42%) and males in the age group of 40-50 years (41%) had higher incidence of subclinical hypothyroidism compared to others. Conclusions: Prevalence of thyroid disorders in diabetics was 45%. Elderly population had more incidences. Sub- clinical hypothyroidism was more common among females.